Mechanisms of effects of phytoestrogens on reproduction, steroidogenesis and steroid action in male rats - McVey, Mark (University of Ottawa (Canada), 2004)
The consequences of soy isoflavone consumption on steroidogenesis were examined in F1 male rats from a multi-generation reproduction study investigating the effects of diets varying in isoflavone content. F1 male rats were obtained from a multi-generation study where the parental generation was fed diets containing alcohol-washed soy protein supplemented with increasing amounts of Novasoy, a commercially available isoflavone supplement. A control group was maintained on a soy-free casein-based diet (AIN93G). Testicular and serum androgen levels were assayed with commercial kits and were approximately doubled at postnatal day (PND) 120 for rats fed a diet of elevated levels of isoflavones. Steroidogenic enzyme activities were significantly increased at PND 28 and immunohistochemistry revealed approximately 25% greater numbers of Leydig cells stained for steroidogenic factor 1 at both PND 28 and 120 amongst rats fed elevated levels of isoflavones, resembling high human consumption rates. These findings show that F1 male rats continuously exposed to a mixture of dietary soy isoflavones from conception onwards exhibit altered gene expression at PND 28, which may lead to increased microsomal steroidogenic enzyme activity at this age and serum and testicular androgen profiles in adulthood. (Abstract shortened by UMI.)
Keywords: Chemistry, Biochemistry.; Health Sciences, Nutrition.